PRACTICI ŞI INOVAŢII ÎN ELABORAREA ŞI EDITAREA VOLUMELOR DE EXEGEZE: (elaborate în Laboratorul de cercetări literare şi biobibliografie „Onisifor Ghibu”) - RĂILEANU, critic şi istoric literar, director al Bibliotecii „Onisifor Ghibu”, Vitalie (BIBLIOPOLIS, 2020)
One of the objective of "Onisifor Ghibu" library is the promotion of scientific publications for different groups of users. To this goal we have utilised different methods and forms of communicating science: book exhibition, book presentations, round tables, creative contests, public lectures, sociological projects. Our scientific activities has been promoted in the blog of the library and social networks.